Alterations of Some Apolipoprotein Levels and ApoE RNA Expression in Iraqi Patients with Chronic Hepatitis B Viral Infection - Amnah Raad Ibrahim; Raghad Hassan Hussein; Athraa Zaidan Hassan (Medical Journal of Babylon)
Background: The high prevalence of hepatitis B virus (HBV) makes it a significant health concern, especially in Iraq. Clinical studies have found that chronic HBV infection affects the occurrence of cardiovascular disease (CVD) by regulating cholesterol metabolism in liver cells. Objective: This study aimed to determine alterations in some serum lipoproteins (ApoA, ApoB, and apolipoprotein E [ApoE]) and oxidized low-density lipoprotein (OxLDL), as well as ApoE gene expression in Iraqi patients with chronic HBV infection, as potential markers for increased cardiovascular risk. Materials and Methods: This case-control study involved fifty patients with chronic HBV admitted to the Gastroenterology and Hepatology Teaching Hospital in Medical city, Baghdad, besides 40 individuals serving as a healthy control group. Results: The current study showed significantly higher levels of ApoA, ApoB, ApoE, and OxLDL among patients compared to the control group. Additionally, HBV patients demonstrated lower expression of ApoE gene in HBV patients. The receiver operating characteristic curve analysis for all parameters showed high sensitivity and specificity, with area under the curve affirming their potential as biomarkers for increased CVD risk in patients with chronic HBV infection. Conclusion: The study reveals significant disparities in plasma levels of ApoA, ApoB, ApoE, and OxLDL between HBV patients and controls, along with reduced ApoE gene expression in these patients, suggesting a potential role of HBV in apolipoproteins dysfunction. Thus, serum ApoA, ApoB, ApoE, and OxLDL in CHB patients may help identify high-risk patients for CVD, thereby preventing the development of CVD or early diagnosis of (CVD) in these patients.